Sheepbulb. - Wong, Li Hua. (2011)
The short film "Sheepbulb" tells the story of a sheep, which is also a bulb, which is also an idea, in its wanderings through a strange and wondrous world on its way to being born. This paper details part of the design process for making the film, with a focus on background design and composition.The animated short film Sheepbulb follows the journey of a strange little sheep through a fantastical landscape in the mind of a child. While the underlying meaning involves the process of idea generation, it also functions as an exploration of the generation of visuals through a mixture of 2-dimensional (2D) and 3- dimensional (3D) media. The final product was animated via 3D software and exported as a 2D layer to be composited with a hand-drawn background.